Determine the scientific foundations for a test designed to measure the level of skill performance of women football players senior - Sabkha, mohamed lamine; hadjar , kherfane mohamed; senouci , abdelkrim (sports creativity, 2025)
Our aim in this study was to define the scientific foundations of a test designed to measure the skill performance of football players in accordance with the principles and stages of designing tests. On this basis we assumed that the skill test has sound scientific foundations and the ability to define standard levels of the designed test that can be worked out, and to verify it we used the descriptive approach in its method The survey, where the sample number was 150 players, was chosen randomly, at the level of the clubs of the first national women's football division in Algeria, and after collecting the results and statistically treating them, a set of results, the most important of which was that the test has high levels of honesty, consistency and objectivity and was identified The standard levels of the test designed,